A glue-free ternary integrated composite lamination for power battery pack

CN123018317APending Publication Date: 2026-10-30FRD SCI & TECH (JIANGSU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611228199.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-13
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0008]现有技术中存在的问题是:现有304不锈钢与热固性聚氨酯玻纤拉挤型材的胶粘连接及螺栓紧固方式均存在可靠性不足、工艺复杂、耐久性差的问题

Benefits of technology

(1)本发明提供的无胶一体化三元复合压条,通过嵌件注塑工艺将复合热塑性材料均匀包裹于304不锈钢压条外表面,再与PU玻纤拉挤型材的凹槽壁面紧密结合,彻底摒弃了传统胶粘剂和螺栓紧固件的使用。该结构从根源上消除了胶层老化、水解脱粘以及螺栓松退、电化学腐蚀等失效模式,有效保障了电池包在全生命周期内的结构完整性和电芯约束可靠性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the technical field of pressing and baling for power battery pack, and particularly relates to a glue-free ternary integrated composite baling for power battery pack. The 304 stainless steel and the thermosetting polyurethane glass fiber pultruded profile are connected by adhesive or bolt fastening, which has insufficient reliability, complex process and poor durability. In view of the above problems, the present application provides a glue-free ternary integrated composite baling for power battery pack, which combines the composite thermoplastic material and the 304 stainless steel baling into an embedded composite part through insert injection molding process, and then the embedded composite part is fixed and bonded with the groove of the PU glass fiber pultruded profile and is heat treated, so as to realize the glue-free and non-porous of the overall structure of the baling. The problem of easy hydrolysis aging and adhesive performance degradation of the adhesive interface in the alternating environment of heat and humidity is fundamentally eliminated, and the stress concentration, cross-section weakening and vibration loosening risk caused by bolt connection are also avoided, so that the structural stability and reliability of the baling under long-term service condition are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of clamping strips for power battery packs, specifically to a glue-free ternary integrated composite clamping strip for power battery packs. Background Technology

[0002] During operation, the cells of a new energy power battery pack undergo repeated volume expansion and contraction due to charge and discharge cycles. Without effective restraint, the relative displacement between cells can lead to module structural instability, fatigue fracture of connecting pieces, and even thermal runaway risks. Therefore, a clamping strip is required inside the battery pack to fix the cells and module frame as a whole. This clamping strip must meet several performance requirements in actual service: sufficient structural rigidity to provide continuous clamping force; excellent electrical insulation to prevent high-voltage short circuits; tolerance to alternating high and low temperature environments ranging from -40℃ to 85℃ or even higher; and the ability to withstand simulated vehicle road vibrations and mechanical impact loads without loosening or failure.

[0003] Currently, the mainstream battery pack clamping strips in the industry use a combination of 304 stainless steel clamping strips and thermosetting polyurethane fiberglass pultruded profiles. The 304 stainless steel clamping strip provides the main mechanical clamping stiffness and structural strength, ensuring reliable constraint of the battery cells; the thermosetting polyurethane fiberglass pultruded profiles utilize their excellent electrical insulation properties and low density to reduce overall weight while achieving insulation protection. Furthermore, the fiberglass-reinforced polyurethane matrix provides good temperature resistance and dimensional stability. The complementary properties of these two materials make this combination the mainstream technical approach in current battery pack clamping strip engineering applications.

[0004] However, with the aforementioned mainstream material combinations, the mutual fixing of 304 stainless steel pressure strips and polyurethane fiberglass pultruded profiles currently relies mainly on two methods: adhesive bonding and mechanical bolt fastening. Both of these connection methods have revealed significant shortcomings in actual production and long-term use.

[0005] In terms of adhesive bonding, stainless steel has low surface energy, and the surface of polyurethane pultruded profiles also exhibits inert characteristics due to the presence of a resin-rich layer, resulting in limited initial bonding strength at the interface. Under the alternating high and low temperatures and continuous vibrations of actual battery pack operation, the adhesive layer is prone to fatigue aging, and its bonding performance significantly deteriorates with prolonged service time. More seriously, the adhesive layer is susceptible to hydrolysis under humid and hot conditions, leading to interface debonding and delamination failure, ultimately resulting in the loss of insulation barrier function and posing a safety hazard. Furthermore, adhesive bonding is an irreversible connection method; the curing process after adhesive application requires a long time and tooling, limiting production cycle time and hindering capacity expansion. Once the bond fails, the pressure strip cannot be disassembled for repair and must be scrapped entirely, increasing after-sales maintenance costs.

[0006] Regarding the mechanical fastening method of bolts, drilling is required in the base material of the pressure strip. Drilling not only weakens the load-bearing cross-section of the stainless steel pressure strip, but also creates stress concentration areas at the hole edges, making it prone to fatigue cracks under vibration loads; drilling through the insulating profile also damages its structural integrity. Under long-term vibration conditions, bolts are at risk of loosening, which will produce abnormal noise, and the decrease in tightening torque will lead to a decrease in clamping force, resulting in a loss of effective constraint on the battery cell. In addition, bolted connections are prone to electrochemical corrosion in humid environments, and moisture seeping in along the bolt holes may also cause a decline in insulation performance. The common problem with both connection methods is that there are many types of connecting components and the assembly process is complicated, which not only affects production efficiency, but also increases the difficulty of quality control.

[0007] In summary, existing adhesive bonding and bolting methods for connecting 304 stainless steel to thermosetting polyurethane fiberglass pultruded profiles suffer from inherent defects such as insufficient reliability, complex processes, and poor durability. Therefore, developing a composite pressure strip solution that can achieve a firm bond between 304 stainless steel pressure strips and thermosetting polyurethane fiberglass pultruded profiles without the need for adhesives and fasteners, while also possessing a highly reliable and efficient molding process, has promising market prospects. Summary of the Invention

[0008] The existing technology suffers from several problems: the adhesive bonding and bolting methods used for connecting 304 stainless steel and thermosetting polyurethane fiberglass pultruded profiles are unreliable, complex, and have poor durability. To address these issues, this invention provides a glue-free ternary integrated composite strip for power battery packs. This composite material is formed through insert injection molding and post-processing. The ternary composite strip comprises a PU fiberglass pultruded profile, a 304 stainless steel strip, and a composite thermoplastic material that bonds and fixes the PU fiberglass pultruded profile and the 304 stainless steel strip. The composite thermoplastic material uniformly coats the outer surface of the 304 stainless steel strip with a thickness of at least 1 mm to form an insert composite. The overall thickness of the 304 stainless steel strip is the same as the length of the PU fiberglass pultruded profile. The PU fiberglass pultruded profile has a uniform thickness. One side of the PU fiberglass pultruded profile has a groove extending along its length, with a U-shaped cross-section. An insert composite is snapped and bonded into the groove of the PU fiberglass pultruded profile. The insert composite is tightly fitted to the inner wall of the groove along its length to form an insert injection-molded composite. The thickness of the insert composite is 1 / 4 to 1 / 3 of the groove depth. After post-processing, the insert injection-molded composite becomes a ternary composite strip. Composite thermoplastic materials are composite materials formed by thermoplastic polymers and glass fibers in a mass ratio of (70-90):(10-30).

[0009] Preferably, the thermoplastic polymer material is PPS or PA66.

[0010] Preferably, the glass fiber is GF30 or GF40.

[0011] Preferably, the thickness of the 304 stainless steel pressure strip is 1.5-3mm.

[0012] Preferably, the thickness of the PU fiberglass pultruded profile is 2-3 mm.

[0013] Preferably, the thickness of the composite thermoplastic material uniformly wrapped around the outer surface of the 304 stainless steel strip is 1-1.5 mm.

[0014] Preferably, the surface roughness Ra of the 304 stainless steel pressure strip is 1.6-3.2 μm.

[0015] Preferably, the PU glass fiber pultruded profile has a glass fiber content of 65%, and the inner wall of the groove is activated by plasma surface activation treatment or by mechanical grinding to remove the resin-rich layer on the surface and then activated by silane coupling agent, or by sandblasting roughening and then activated by silane coupling agent.

[0016] Preferably, the post-treatment involves annealing the insert injection-molded composite at a constant temperature of 90-150°C for 2-6 hours.

[0017] Beneficial effects: (1) The adhesive-free integrated ternary composite strip provided by the present invention uniformly wraps the composite thermoplastic material on the outer surface of the 304 stainless steel strip through an insert injection molding process, and then tightly bonds it with the groove wall of the PU glass fiber pultruded profile, completely eliminating the use of traditional adhesives and bolt fasteners. This structure eliminates failure modes such as adhesive aging, hydrolysis debonding, bolt loosening, and electrochemical corrosion from the root, effectively ensuring the structural integrity of the battery pack and the reliability of cell constraints throughout its entire life cycle.

[0018] (2) The composite thermoplastic material is made by compounding thermoplastic polymers and glass fibers in a specific ratio. It forms a strong physical coating and interfacial bond with the surface of the stainless steel strip, avoiding the problem of insufficient bonding strength caused by the low surface energy of stainless steel. At the same time, the composite thermoplastic material fills the groove of the PU glass fiber pultruded profile and fits tightly with its wall. It fully fills the micro-gaps of the interface by utilizing the melt flow characteristics during injection molding. After cooling, it forms a reliable mechanical lock and interfacial adhesion, so that the three materials can be integrated and fixed without adhesives and fasteners. The stainless steel strip, as a skeleton, provides overall bending stiffness and clamping force. The composite thermoplastic material, as an interfacial transition layer, evenly transfers the load to the PU glass fiber pultruded profile, while the PU glass fiber pultruded profile gives full play to its advantages in electrical insulation and temperature resistance. The three work together to retain the performance advantages of the two main materials and solve the problem of effective fixing between dissimilar materials through the composite thermoplastic material, so that the strip can maintain long-term stability under vibration and alternating loads.

[0019] (3) The structure of the insert composite part being 1 / 4 to 1 / 3 of the groove depth of the PU glass fiber pultruded profile makes the composite thermoplastic material form a local protrusion in the groove. After injection molding and cooling, the protrusion generates a certain pre-compression contact stress, which enhances the tightness of the fit between the insert composite part and the groove wall, further improving the interface shear resistance. At the same time, the protrusion structure can play an auxiliary load-bearing role when the pressure strip is under pressure, and slow down the relative slippage trend between the stainless steel pressure strip and the PU glass fiber pultruded profile.

[0020] (4) The present invention adopts the insert injection molding process for one-time molding. The entire fixing process is completed simultaneously with the injection molding, without the need for additional processes such as gluing, curing, drilling, and bolt tightening, which simplifies the production process and shortens the manufacturing cycle of a single part. The injection molding process is easy to automate mass production, with good quality consistency, which helps to reduce manufacturing costs and quality control difficulties.

[0021] (5) In the post-processing step, the insert injection molding composite is annealed at a specific temperature for a certain period of time, which can effectively eliminate the residual stress generated by the cooling shrinkage inside the composite thermoplastic material during the injection molding process, and at the same time promote the further relaxation and rearrangement of polymer chain segments, improve the bonding stability of the composite thermoplastic material and stainless steel interface, and ensure that the pressure strip does not warp or peel off under long-term high and low temperature alternating environment.

[0022] (6) When PPS or PA66 is used as the matrix resin in composite thermoplastic materials, both types of materials have excellent thermal stability and chemical resistance. PPS has better high temperature resistance and dimensional stability, while PA66 has better toughness and cost advantage. It can be flexibly selected according to specific working conditions. Using GF30 or GF40 as the reinforcing phase can significantly improve the elastic modulus and creep resistance of composite thermoplastic materials, ensuring that they do not experience significant stress relaxation under long-term compression force, so that the battery cell is always kept in an effective constrained state.

[0023] (7) The present invention can significantly improve the surface energy of the groove wall and increase the number of active functional groups by performing plasma surface activation treatment, mechanical grinding to remove the resin-rich layer on the surface and then activation treatment with silane coupling agent, or sandblasting roughening and then activation treatment with silane coupling agent. This improves the wettability and chemical bonding between the composite thermoplastic material melt and the PU glass fiber pultruded profile, and improves the interfacial bonding strength between the two from physical locking to chemical bonding level, effectively preventing the degradation of interfacial performance under humid heat aging conditions.

[0024] (8) The surface roughness of the stainless steel pressure strip is controlled within the range of Ra=1.6~3.2μm, which ensures that the composite thermoplastic material can penetrate into the surface micro grooves to form mechanical anchoring when it melts and fills, and avoids incomplete melt filling and local pore defects caused by excessive surface roughness, thus taking into account both the interface bonding strength and the injection molding quality.

[0025] (9) After the ternary composite strip obtained by the present invention is assembled inside the battery pack, the composite thermoplastic material is continuously and uniformly coated on the surface of the stainless steel strip. Even under extreme temperature cycling, since the linear expansion coefficient of the composite thermoplastic material is between that of stainless steel and PU glass fiber pultruded profile, it can play a stress buffer and transition role in the process of thermal expansion and contraction, reduce the interfacial thermal stress caused by the mismatch of thermal expansion coefficients, and improve the dimensional stability and thermal fatigue resistance of the overall structure in a wide temperature range. Attached Figure Description Figure 1 Example 1: A schematic diagram of the structure of the glue-free ternary integrated composite pressure strip for the power battery pack. Detailed Implementation

[0026] The present invention will be described in detail below with reference to embodiments. However, it should be understood that the following embodiments are merely illustrative examples of implementation of the present invention and are not intended to limit the scope of the present invention.

[0027] The composite thermoplastic material used in the following embodiments of the present invention is PPS-GF40, purchased from Kingfa Science & Technology Co., Ltd., and the purchased model is PPS-GF40. The PU glass fiber pultruded profiles (2.5mm thick rectangular strips) used in the following embodiments of the present invention have a glass fiber content of 60-70% and were purchased from Chongqing Kexin Company, internal model 236.

[0028] The preparation method of the KH550 silane coupling agent solution used in the following embodiments of the present invention is as follows: KH550 was added to a mixed solvent of anhydrous ethanol and deionized water at a volume ratio of 1:6 to obtain a KH550 silane coupling agent solution with a mass concentration of 0.5%.

[0029] Example 1 The preparation method of a glue-free ternary integrated composite pressure strip for power battery packs is as follows: Materials preparation: (1) A 2mm thick 304 stainless steel plate is stamped into a long strip and the surface is laser etched to have a uniform frosted effect, and finally a 304 stainless steel strip with an overall surface roughness Ra=2.0 is obtained. (2) The PU glass fiber pultruded profile (glass fiber content 65%) is exposed by mechanically grinding the pure resin layer on one side. Then, the PU glass fiber pultruded profile is processed by extrusion into a PU glass fiber pultruded profile with a groove extending along its length on one side. The groove has a U-shaped cross-section. Finally, KH550 silane coupling agent solution is uniformly sprayed on the inner wall of the groove, and then dried at 70℃ for 2h to obtain KH550 modified PU glass fiber pultruded profile; the thickness of the KH550 modified layer is 0.05μm. Insert injection molding: (1) A 304 stainless steel strip (2.0 mm thick and 40 mm wide) with laser etching treatment is used as an insert. The 304 stainless steel strip is the same length as the PU glass fiber pultruded profile. The composite thermoplastic material is PA66-GF30, which is purchased from Kingfa Science & Technology Co., Ltd. (2) To ensure accurate positioning of the pressure strip during injection molding, a φ2.0mm positioning hole is opened at each end of the stainless steel pressure strip along its length. Positioning pins are set at corresponding positions in the mold, with a positioning accuracy requirement of ≤0.1mm. The KH550 modified PU fiberglass pultruded profile, 304 stainless steel pressure strip, and composite thermoplastic material are combined using an insert injection molding process, so that the composite thermoplastic material is uniformly wrapped around the outer surface of the 304 stainless steel pressure strip with a thickness of 1mm to form an insert composite. The insert composite is snapped and bonded to the groove of the KH550 modified PU fiberglass pultruded profile. The groove depth is designed to be 3.2mm. The insert composite is tightly fitted to the inner wall of the groove along its length to obtain the insert injection molding composite. The exposed part of the insert composite is 0.8mm higher than the groove.

[0030] Post-processing: The insert injection-molded composite is annealed in a 100℃ oven for 4 hours to eliminate internal stress, thus obtaining the glue-free ternary integrated composite strip for power battery packs.

[0031] A schematic diagram of the adhesive-free ternary integrated composite pressure strip for the power battery pack obtained in Example 1 is shown in the attached instruction manual. Figure 1 As shown.

[0032] Example 2 The preparation method of a glue-free ternary integrated composite pressure strip for power battery packs is as follows: Materials preparation: (1) A 1.5mm thick 304 stainless steel plate is stamped into a long strip and the surface is laser etched to have a uniform frosted effect, and finally a 304 stainless steel strip with an overall surface roughness Ra=3.2 is obtained. (2) The PU glass fiber pultruded profile (glass fiber content 70%) is exposed by mechanically grinding the pure resin layer on one side. Then, the PU glass fiber pultruded profile is processed by extrusion process to form a PU glass fiber pultruded profile with a groove extending along its length on one side. The groove has a U-shaped cross-section. Finally, KH550 silane coupling agent solution is uniformly sprayed on the inner wall of the groove, and then dried at 80℃ for 1.5h to obtain KH550 modified PU glass fiber pultruded profile; the thickness of the KH550 modified layer is 0.1μm. Insert injection molding: (1) A 304 stainless steel strip (2.0 mm thick and 50 mm wide) with laser etching treatment is used as an insert. The 304 stainless steel strip is the same length as the PU glass fiber pultruded profile; the composite thermoplastic material is PPS-GF40; (2) To ensure accurate positioning of the pressure strip during injection molding, a φ2.0mm positioning hole is opened at each end of the stainless steel pressure strip along its length. Positioning pins are set at corresponding positions in the mold, with a positioning accuracy requirement of ≤0.1mm. The KH550 modified PU fiberglass pultruded profile, 304 stainless steel pressure strip, and composite thermoplastic material are combined using an insert injection molding process, so that the composite thermoplastic material is uniformly wrapped around the outer surface of the 304 stainless steel pressure strip with a thickness of 1.35mm to form an insert composite. The insert composite is snapped and bonded to the groove of the KH550 modified PU fiberglass pultruded profile. The groove depth is designed to be 3.6mm. The insert composite fits tightly against the inner wall of the groove along its length, with its exposed part protruding 1.1mm above the groove.

[0033] Post-processing: The insert injection-molded composite is annealed in a 100℃ oven for 4 hours to eliminate internal stress, thus obtaining the glue-free ternary integrated composite strip for power battery packs.

[0034] Example 3 The preparation method of a glue-free ternary integrated composite pressure strip for power battery packs is as follows: Materials preparation: (1) Using 3mm thick 304 stainless steel plate, a long strip is formed by stamping, and the surface is laser etched to form a uniform frosted effect, finally obtaining a 304 stainless steel strip with an overall surface roughness Ra=3.2; (2) The PU glass fiber pultruded profile (glass fiber content 60%) is exposed by mechanically grinding the pure resin layer on one side. Then, the PU glass fiber pultruded profile is processed by extrusion process to form a PU glass fiber pultruded profile with a groove extending along its length on one side. The groove has a U-shaped cross-section. Finally, KH550 silane coupling agent solution is uniformly sprayed on the inner wall of the groove, and then dried at 75℃ for 2h to obtain KH550 modified PU glass fiber pultruded profile; the thickness of the KH550 modified layer is 0.2μm. Insert injection molding: (1) A 304 stainless steel strip (3.0 mm thick and 50 mm wide) with laser etching treatment was used as an insert. The 304 stainless steel strip was the same length as the PU glass fiber pultruded profile; the composite thermoplastic material was PA66-GF30, purchased from Kingfa Science & Technology Co., Ltd. (2) To ensure accurate positioning of the pressure strip during injection molding, a φ2.0mm positioning hole is opened at each end of the stainless steel pressure strip along its length. Positioning pins are set at corresponding positions in the mold, with a positioning accuracy requirement of ≤0.1mm. The KH550 modified PU fiberglass pultruded profile, 304 stainless steel pressure strip, and composite thermoplastic material are combined using an insert injection molding process, so that the composite thermoplastic material is uniformly wrapped around the outer surface of the 304 stainless steel pressure strip with a thickness of 1.5mm to form an insert composite. The insert composite is snapped and bonded to the groove of the KH550 modified PU fiberglass pultruded profile. The groove depth is designed to be 4.6mm. The insert composite fits tightly against the inner wall of the groove along its length, with its exposed part protruding 1.4mm above the groove.

[0035] Post-processing: The insert injection-molded composite is annealed in a 110℃ oven for 3 hours to eliminate internal stress, thus obtaining the glue-free ternary integrated composite strip for power battery packs.

[0036] Example 4 The preparation method of a glue-free ternary integrated composite pressure strip for power battery packs is as follows: Materials preparation: (1) A 1.5mm thick 304 stainless steel plate is stamped into a long strip and the surface is laser etched to have a uniform frosted effect, and finally a 304 stainless steel strip with an overall surface roughness Ra=1.6 is obtained. (2) The PU glass fiber pultruded profile (glass fiber content 65%) is exposed by mechanically grinding the pure resin layer on one side. Then, the PU glass fiber pultruded profile is processed by extrusion process to form a PU glass fiber pultruded profile with a groove extending along its length on one side. The groove has a U-shaped cross-section. Finally, KH550 silane coupling agent solution is uniformly sprayed on the inner wall of the groove, and then dried at 75℃ for 2h to obtain KH550 modified PU glass fiber pultruded profile; the thickness of the KH550 modified layer is 0.2μm. Insert injection molding: (1) A 304 stainless steel strip (1.5 mm thick and 40 mm wide) with laser etching treatment was used as an insert. The 304 stainless steel strip was the same length as the PU glass fiber pultruded profile; the composite thermoplastic material was PA66-GF30, purchased from Kingfa Science & Technology Co., Ltd. (2) To ensure accurate positioning of the pressure strip during injection molding, a φ2.0mm positioning hole is opened at each end of the stainless steel pressure strip along its length. Positioning pins are set at corresponding positions in the mold, with a positioning accuracy requirement of ≤0.1mm. The KH550 modified PU fiberglass pultruded profile, 304 stainless steel pressure strip, and composite thermoplastic material are combined using an insert injection molding process, so that the composite thermoplastic material is uniformly wrapped around the outer surface of the 304 stainless steel pressure strip with a thickness of 0.8mm to form an insert composite. The insert composite is snapped and bonded to the groove of the KH550 modified PU fiberglass pultruded profile. The groove depth is designed to be 2.48mm. The insert composite fits tightly against the inner wall of the groove along its length, with its exposed part protruding 0.62mm above the groove.

[0037] Post-processing: The insert injection-molded composite is annealed in a 90℃ oven for 2 hours to eliminate internal stress, thus obtaining the glue-free ternary integrated composite strip for power battery packs.

[0038] Comparative Example 1 is the same as Example 1, except that the PU fiberglass pultruded profile in Comparative Example 1 is not subject to any surface treatment, and the surface of the 304 stainless steel strip is not subject to laser etching treatment.

[0039] Comparative Example 2 The same PU fiberglass pultruded profile and 304 stainless steel strip with the same dimensions as in Example 1 were used. The two were directly bonded together with epoxy structural adhesive (Henkel Loctite EA 9492 two-component epoxy structural adhesive) and then cured at room temperature for 24 hours.

[0040] Performance testing The composite pressure strips obtained in the embodiments and comparative examples of the present invention were subjected to relevant performance tests, and the test results are shown in Table 1.

[0041] Table 1 In Table 1, "-" indicates that the group has no corresponding structure and the test was not conducted.

[0042] Based on the above-described preferred embodiments of the present invention, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.

Claims

1. A glue-free ternary integrated composite batten for power battery pack, characterized in that, It is a composite material formed by insert injection molding and post-processing. The ternary composite strip includes a PU glass fiber pultruded profile, a 304 stainless steel strip, and a composite thermoplastic material that bonds and fixes the PU glass fiber pultruded profile and the 304 stainless steel strip. The composite thermoplastic material is uniformly wrapped around the outer surface of the 304 stainless steel strip with a thickness of at least 1 mm to form an insert composite part. The overall thickness of the 304 stainless steel strip is the same and the same length as the PU glass fiber pultruded profile. The PU fiberglass pultruded profile has a uniform thickness. One side of the PU fiberglass pultruded profile has a groove extending along its length, with a U-shaped cross-section. An insert composite is snapped and bonded into the groove of the PU fiberglass pultruded profile. The insert composite is tightly fitted to the inner wall of the groove along its length to form an insert injection-molded composite. The thickness of the insert composite is 1 / 4 to 1 / 3 of the groove depth. After post-processing, the insert injection-molded composite becomes a ternary composite strip. Composite thermoplastic materials are composite materials formed by thermoplastic polymers and glass fibers in a mass ratio of (70-90):(10-30).

2. The adhesive-free ternary integrated composite pressure strip for a power battery pack according to claim 1, characterized in that, The thermoplastic polymer material is PPS or PA66.

3. The adhesive-free ternary integrated composite pressure strip for a power battery pack according to claim 1, characterized in that, The glass fiber is GF30 or GF40.

4. The adhesive-free ternary integrated composite pressure strip for a power battery pack according to claim 1, characterized in that, The thickness of 304 stainless steel pressure strips is 1.5-3mm.

5. The adhesive-free ternary integrated composite pressure strip for a power battery pack according to claim 1, characterized in that, The thickness of PU fiberglass pultruded profiles is 2-3mm.

6. The adhesive-free ternary integrated composite pressure strip for a power battery pack according to claim 1, characterized in that, The composite thermoplastic material is uniformly wrapped around the outer surface of the 304 stainless steel strip with a thickness of 1-1.5mm.

7. The adhesive-free ternary integrated composite pressure strip for a power battery pack according to claim 1, characterized in that, The surface roughness of 304 stainless steel pressure strips is Ra=1.6-3.2μm.

8. The adhesive-free ternary integrated composite pressure strip for a power battery pack according to claim 1, characterized in that, The PU glass fiber pultruded profile has a glass fiber content of 65%. The inner wall of the groove is activated by plasma surface treatment or by mechanical grinding to remove the resin-rich layer on the surface and then activated by silane coupling agent, or by sandblasting roughening and then activated by silane coupling agent.

9. The adhesive-free ternary integrated composite pressure strip for a power battery pack according to claim 1, characterized in that, The post-treatment involves annealing the insert injection-molded composite at a constant temperature of 90-150℃ for 2-6 hours.